The Role of Obesity in the Poor Prognosis of COVID-19 Infection: A Review of 192 Patients - Ziad Feghaly; Rany Aoun; Christian Mouawad; Bilal Chamaa; Houssam Dahboul; Serge Kassar; Michael Osseis; Roger Noun; Ghassan Chakhtoura (Interdisciplinary Perspectives on Infectious Diseases)
Context. COVID-19 pandemic affects the whole world and continues to impact the health system daily. It also led to a high rate of hospitalizations, some of which required admission to the intensive care units. At the same time, obesity has been a major health problem for many years and continues to worsen. These two pandemics appear to be converging since obesity increasingly appears to be a poor prognostic factor for COVID-19 infection. Methods. We performed a retrospective study on all patients having COVID-19 infection and admitted to our institution between March 2020 and June 2021. Inclusion criteria included any patient over the age of 18 admitted to our institution’s COVID-19 unit, or intensive care unit, with a positive COVID-19 PCR or positive COVID-19 serology (IgM). Results. 192 patients met the inclusion criteria, with an average age of 62.68 years and a slight male predominance (64.58%). 76.04% of hospitalized patients and 80% of those admitted to the ICU were either overweight or obese. No statistically significant difference was found regarding the risk of in-hospital mortality and invasive ventilation. The same applies to the length of stay, admission to intensive care, O2 needs, and for the various complications (all p values were >0.05). Patients with obesity type II and III have an increased risk of cardiac arrests and need for intubation and mechanical ventilation. Conclusion. Obesity tends to be a major risk factor for a pejorative evolution in the COVID-19 infection.